Effect of Solid Digestate Amendment on the Dynamics of N Soluble Forms in Two Contrasting Soil Profiles under Mediterranean Environment - Giuseppe Badagliacca; Emilio Lo Presti; Antonio Gelsomino; Michele Monti (Agriculture, 2023)
Use of solid agricultural digestate as a substitute for chemical fertilizers in Mediterranean cropping systems can be a valuable approach to improving soil fertility. However, it is important to accurately assess its mineralisation dynamics in order to avoid uncontrolled nutrient releases in agroecosystems. With this aim, a field experiment was conducted to evaluate the effects of solid digestate application on total soil nitrogen (TSN), extractable organic N (EON) and mineral N forms (NH4+-N and NO3−-N) in two Mediterranean soil profiles (clay and sandy-loam) over one year. The solid digestate increased TSN and EON concentrations in the upper soil layer (0–20 cm) of both soils, more in the clay soil, with a decreasing effect in the lower soil layers (20–40 and 40–60 cm). The amendment increased NH4+-N concentrations, with a greater and longer-lasting effect in the clay soil, especially in the first two soil layers (0–20 and 20–40 cm), while in the lowest, it was limited at the first sampling epoch. The NO3−-N copied the NH4+-N trends in both soils, with a greater effect on the 0–20 cm soil layer at all sampling epochs. The present study suggests that solid digestate, applied at a dose of 30 Mg ha−1, can be a useful alternative to mineral N fertilisers for clay and sandy-loam soils in Mediterranean orchards.